Radical-induced dissociation leading to the loss of CO2 from the oxazolone ring of [b5 − H]˙+ ions. Issue 27 (21st June 2016) - Lau, Justin Kai-Chi; Zhao, Junfang; Williams, Declan; Wu, Bai-Han Backen; Wang, Yating; Mädler, Stefanie; Saminathan, Irine S.; Siu, K. W. Michael; Hopkinson, Alan C.
Abstract : The radical adjacent to the oxazolone ring induces loss of CO2 compared with the loss of CO observed from closed-shell [b n ] + ions. Abstract : Macrocyclization is commonly observed in large b n + ( n ≥ 4) ions and as a consequence can lead to incorrect protein identification due to sequence scrambling. In this work, the analogous [b5 − H]˙ + radical cations derived from aliphatic hexapeptides (GA5 ˙ + ) also showed evidence of macrocyclization under CID conditions. However, the major fragmentation for [b5 − H]˙ + ions is the loss of CO2 and not CO loss, which is commonly observed in closed-shell b n + ions. Isotopic labeling using CD3 and 18 O revealed that more than one common structure underwent dissociations. Theoretical studies found that the loss of CO2 is radical-driven and is facilitated by the radical being located at the Cα atom immediately adjacent to the oxazolone ring. Comparable energy barriers against macrocyclization, hydrogen-atom transfer, and fragmentations are found by DFT calculations and the results are consistent with the experimental observations that a variety of dissociation products are observed in the CID spectra.